Efficacy and Safety of a Novel Pegylated Interferon Alpha-2a in Egyptian Patients with Genotype 4 Chronic Hepatitis C - Alaa Awad Taha; Ahmad El-Ray; Maged El-Ghannam; Bahaa Mounir (Canadian Journal of Gastroenterology)
BACKGROUND: Hepatitis C virus (HCV) genotype 4 is a common infection in Egypt and is the leading cause of liver disease.